Distribution of High-Volume Ankle Replacement Surgeons in United States Metropolitan Areas. Issue 2 (April 2022) - Stein, Brandon; Somerson, Jeremy; Janney, Cory; Panchbhavi, Vinod
Background: Ankle osteoarthritis is increasing, thus creating greater demand for high-volume total ankle arthroplasty (TAA) surgeons. The Medicare Provider Utilization and Payment Data Public Use File (MPUPD-PUF) provides volume and reimbursement data for procedures performed by physicians participating in Medicare. This study analyzes surgeon prevalence, surgeon distribution, and factors affecting surgeon prevalence in metropolitan areas. Methods: The MPUPD-PUF was reviewed from 2012 to 2015, and data were extracted for physicians performing ≥11 TAA procedures. Physicians in metropolitan areas (population >1 million) were grouped together, and reimbursement, number of high-volume surgeons, and procedures were calculated. Presence of an American Orthopaedic Foot and Ankle Society (AOFAS) fellowship program was analyzed for associations with high-volume TAA surgeons. Results: Fifty-three surgeons performed ≥11 TAA procedures (1, 960 total) covered by Medicare. Of these surgeons, 66% practice in metropolitan areas with a population >1 million. Fifty-one percent of US major metropolitan areas contained no surgeon who submitted >10 traditional Medicare claims for TAA. Areas with an AOFAS fellowship had nominally more TAA claims submitted. Conclusions: The distribution of high-volume TAA surgeons among major metropolitan areas in the United States is highly unequal. Analyzing the data with this method aids in targeting TAA surgeons to currently underserved areas. Levels of Evidence: Level IV: Retrospective-comparative study